2017
DOI: 10.1073/pnas.1614412114
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and efficient generation of oligodendrocytes from human induced pluripotent stem cells using transcription factors

Abstract: Rapid and efficient protocols to generate oligodendrocytes (OL) from human induced pluripotent stem cells (iPSC) are currently lacking, but may be a key technology to understand the biology of myelin diseases and to develop treatments for such disorders. Here, we demonstrate that the induction of three transcription factors (SOX10, OLIG2, NKX6.2) in iPSC-derived neural progenitor cells is sufficient to rapidly generate O4 OL with an efficiency of up to 70% in 28 d and a global gene-expression profile comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
242
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 208 publications
(267 citation statements)
references
References 51 publications
(85 reference statements)
5
242
0
Order By: Relevance
“…Initial publications demonstrated that overexpression of OLIG2 or SOX10 can promote the differentiation of human fetal NPC into OPC in vitro as well as their differentiation into MBP+ myelin‐forming cells after transplantation (Maire et al, ; Wang et al, ). We showed that combining the overexpression of SOX10, OLIG2 and NKX6.2 in iPSC derived NPC facilitated OPC specification and led to generation of 70% O4+ cells within 28 days (Ehrlich et al, ) (Figure ). One year later, Garcia‐Leon et al reduced the cocktail of transcription factors by showing that SOX10 alone was sufficient to generate 50 to 60% O4+ cells in 22 days upon iPSC differentiation (Garcia‐Leon et al, ).…”
Section: Generation Of Oligodendrocytes From Pluripotent Cellsmentioning
confidence: 96%
“…Initial publications demonstrated that overexpression of OLIG2 or SOX10 can promote the differentiation of human fetal NPC into OPC in vitro as well as their differentiation into MBP+ myelin‐forming cells after transplantation (Maire et al, ; Wang et al, ). We showed that combining the overexpression of SOX10, OLIG2 and NKX6.2 in iPSC derived NPC facilitated OPC specification and led to generation of 70% O4+ cells within 28 days (Ehrlich et al, ) (Figure ). One year later, Garcia‐Leon et al reduced the cocktail of transcription factors by showing that SOX10 alone was sufficient to generate 50 to 60% O4+ cells in 22 days upon iPSC differentiation (Garcia‐Leon et al, ).…”
Section: Generation Of Oligodendrocytes From Pluripotent Cellsmentioning
confidence: 96%
“…S6B). To extend the analysis to human cells, we generated oligodendrocytes from induced pluripotent human stem cells (iPSCs) derived from healthy human adults (29). We found that BCAS1 was expressed in 86.1 ± 2.3% of the O4 + oligodendrocytes with arborized morphology at 24 days in vitro ( fig.…”
Section: Bcas1 + Cells Represent a Transient Population Of Oligodendrmentioning
confidence: 99%
“…While most oligodendrocyte differentiation protocols take a long period of time (60-150 days; e.g.) and show limited efficiency (Wang et al, 2013;Douvaras et al, 2014;Djelloul et al, 2015), a recent protocol published in PNAS allows rapid and efficient generation of oligodendrocytes from hiPSC (Ehrlich et al, 2017). …”
Section: Published In Vitro Methods Beyond Chemical Testingmentioning
confidence: 99%